2022
DOI: 10.3389/fpsyt.2022.890840
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mortality From Novel Psychoactive Substances as “Legal Highs”: Gender Differences in Manner of Death and Implications for Risk Differences for Women

Abstract: IntroductionThis study aimed to examine drug-related deaths in the UK in which novel psychoactive substances (NPS) are an implicated substance, and to focus on female deaths in comparison with male deaths. While male overdoses dominate epidemiological statistics, there is an increase in female drug-related deaths and a narrowing of the gap between gender mortality rates which is to date unexplained.MethodThis study analyzed data from the National Programme for Substance Abuse Deaths (NPSAD) database that recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…It is noteworthy that diminishing gender differences have also been reported in the use of other illicit drugs, such as cannabis among the Japanese general population, 15 party drugs among Dutch university students, 17 heroin and opioid analgesics in the United States over the past decade, 31 , 32 and NPS-related deaths in the United Kingdom. 33 Similar trends were also found in problematic alcohol use in Taiwan 34 and other East Asian countries. 35 , 36 Whether changes in gender roles were associated with the phenomenon of gender convergence in various substance uses warrants future investigation.…”
Section: Discussionsupporting
confidence: 59%
“…It is noteworthy that diminishing gender differences have also been reported in the use of other illicit drugs, such as cannabis among the Japanese general population, 15 party drugs among Dutch university students, 17 heroin and opioid analgesics in the United States over the past decade, 31 , 32 and NPS-related deaths in the United Kingdom. 33 Similar trends were also found in problematic alcohol use in Taiwan 34 and other East Asian countries. 35 , 36 Whether changes in gender roles were associated with the phenomenon of gender convergence in various substance uses warrants future investigation.…”
Section: Discussionsupporting
confidence: 59%
“…Knowledge of the pharmacological effects of new emerging drugs is, therefore, essential to managing the clinical symptoms of intoxicated patients presenting at emergency centers. Notably, differences started being reported in the use [ 11 ] and effects [ 12 , 13 ] of NPSs in males and females, with women using NPSs in association with illicit and/or over-the-counter drugs more than men [ 14 ]. Preclinical studies confirmed significant sex-dependent differences in the action of novel cathinones [ 15 ] and phenethylamines [ 16 ] on the brain, in line with the vast literature reporting important sex (in animals) and gender (in humans) differences in drug addiction [ 17 ] and in other addictive behaviors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%